2021
DOI: 10.12974/2313-1047.2021.08.2
|View full text |Cite
|
Sign up to set email alerts
|

Borderline and Antisocial Personality Disorders in the Bible

Abstract: Introduction: A pervasive and inflexible personality characterizes the borderline personality disorder (BPD) and antisocial personality disorder (ASPD). Both belong to cluster B of the personality classification, and the main feature is emotional dysregulation and a high degree of impulsivity. Objective: To present, outline, and discuss the traits of borderline and antisocial personalities in the biblical characters. Methods: An extensive search was conducted in the Old and New Testaments to find characters wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Martins HAL, Martins BBM, Santos CC, Pontes J, Oliveira DA, Valença MM Persistent idiopathic facial pain associated with borderline personality disorder: a case report Know about emotional dysregulation is crucial to understand BPD. 8 The patient described in this study showed severe emotional instability, crises of unmotivated anger, and binge eating. Many patients with BPD manifest emotional dysregulation by alcohol and drug abuse, leading to substance dependence.…”
Section: Asaamentioning
confidence: 66%
See 1 more Smart Citation
“…Martins HAL, Martins BBM, Santos CC, Pontes J, Oliveira DA, Valença MM Persistent idiopathic facial pain associated with borderline personality disorder: a case report Know about emotional dysregulation is crucial to understand BPD. 8 The patient described in this study showed severe emotional instability, crises of unmotivated anger, and binge eating. Many patients with BPD manifest emotional dysregulation by alcohol and drug abuse, leading to substance dependence.…”
Section: Asaamentioning
confidence: 66%
“…Non-lethal attempt methods sometimes follow suicidal ideation (e.g., excessive medication-taking at once) or violent methods, such as hanging, jumping from high places, throwing themselves in front of automobiles at high speed, and self-harm with knives or firearms. [6][7][8] Studies observed a 30% prevalence rate of BPD among patients with chronic pain. Pain scores are higher in patients with chronic pain and BPD than those patients without BPD.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Borderline disorder is often diagnosed in late adolescence or young adulthood, and symptoms result from emotional dysregulation, such as irritability, frequent mood swings, impulsivity, anger outbursts, and difficulties in interpersonal relationships. 7,8 Therefore, DMDD and borderline symptoms overlap, as demonstrated in Figure 1. Considering DMDD diagnosis was described eight years ago in the DSM-5 and symptoms are developed during childhood, we do not have sufficiently follow-up studies to understand the personality of these patients in adulthood.…”
Section: Introductionmentioning
confidence: 92%